2015
DOI: 10.1136/bjsports-2015-094921
|View full text |Cite
|
Sign up to set email alerts
|

Exercise level before pregnancy and engaging in high-impact sports reduce the risk of pelvic girdle pain: a population-based cohort study of 39 184 women

Abstract: Women who exercise regularly and engage in high-impact exercises before the first pregnancy may have a reduced risk of pelvic girdle pain in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…In contrast, our meta-analysis suggested no effect of exercise on pelvic girdle pain during pregnancy, although an earlier prospective cohort study of 39,184 nulliparous women had found that pre-pregnancy exercise for 3-5 times/week reduces the risk of pelvic girdle pain during pregnancy by 14% (Owe et al, 2016). The discrepancy may have occurred because the interventions in the trials that were included in the current review did not start until the second trimester.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast, our meta-analysis suggested no effect of exercise on pelvic girdle pain during pregnancy, although an earlier prospective cohort study of 39,184 nulliparous women had found that pre-pregnancy exercise for 3-5 times/week reduces the risk of pelvic girdle pain during pregnancy by 14% (Owe et al, 2016). The discrepancy may have occurred because the interventions in the trials that were included in the current review did not start until the second trimester.…”
Section: Discussioncontrasting
confidence: 68%
“…Lumbopelvic pain, defined as pain in the low back (lumbar region) and/or pelvic girdle (symphysis pubis, sacroiliac joint and gluteal region) (Wu et al, 2004), is the most common musculoskeletal complaint in pregnancy (Vermani et al, 2010). More than half of pregnant women experience low back pain (Kovacs et al, 2012;Gjestland et al, 2013), and 10-65% pelvic girdle pain (Vleeming et al, 2008;Kovacs et al, 2012;Gjestland et al, 2013;Owe et al, 2016). Moreover, the pain is frequently rated as moderate to severe (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Women who reported high-impact exercise 3–5 times per week before pregnancy had a 14% lower risk of developing severe PGP in pregnancy compared with non-exercisers 296. In a longitudinal cohort study, a greater loss of physical condition seems not to be a cause but rather a consequence of LBP and/or PGP in pregnancy,297 hence knowledge about type of exercise and dose is needed.…”
Section: Pregnancymentioning
confidence: 99%
“…Whether other life style factors, such as leisure-time physical activity (LTPA) are associated with the development of HG, has not yet been studied. It is, however, well known that LTPA before pregnancy reduces the risk of other pregnancy-related conditions, such as gestational diabetes 11 , pelvic girdle pain 12 , and hypertensive disorders including preeclampsia 13 14 . These conditions are all previously reported to be associated with HG [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%